Identification and Characterization of Mycobacterium tuberculosis Beijing Genotype Strain SBH163, Isolated in Sabah, Malaysia - Jaeyres Jani; Siti Fatimah Abu Bakar; Zainal Arifin Mustapha; Chin, Kai Ling; Roddy Teo; Kamruddin Ahmed (2020)
This is a report on the whole-genome sequence of Mycobacterium tuberculosis strain SBH163, which was isolated from a patient in the Malaysian Borneo state of Sabah. This report provides insight into the molecular characteristics of an M. tuberculosis Beijing genotype strain related to strains from Russia and South Africa.